Predicted and observed therapeutic dose exceedances of ionizable pharmaceuticals in fish plasma from urban coastal systems. (19th January 2016) - Scott, W. Casan; Du, Bowen; Haddad, Samuel P.; Breed, Christopher S.; Saari, Gavin N.; Kelly, Martin; Broach, Linda; Chambliss, C. Kevin; Brooks, Bryan W.
Abstract: Instream flows of the rapidly urbanizing watersheds and estuaries of the Gulf of Mexico in Texas (USA) are increasingly dominated by reclaimed waters. Though ionizable pharmaceuticals have received increasing attention in freshwaters, many research questions remain unanswered, particularly in tidally influenced urban coastal systems, which experience significant spatiotemporal variability in pH that influences bioavailability and bioaccumulation. The authors coupled fish plasma modeling of therapeutic hazard values with field monitoring of water chemistry variability and pharmaceutical occurrence to examine whether therapeutic hazards to fish existed within these urban coastal ecosystems and whether therapeutic hazards differed within and among coastal locations and seasons. Spatial and temporal fluctuations in pH within study sites altered the probability of encountering pharmaceutical hazards to fish. Significant water quality differences were consistently observed among traditional parameters and pharmaceuticals collected from surface and bottom waters, which are rarely sampled during routine surface water quality assessments. The authors then compared modeling predictions of fish plasma concentrations of pharmaceuticals to measured plasma levels from various field‐collected fish species. Diphenhydramine and diltiazem were observed in plasma of multiple species, and diltiazem exceeded human therapeutic doses in largemouth bass, catfish, and mullet inhabiting these urban estuaries. Though the present study only examined a small number of target analytes, which represent a microcosm of the exposome of these fish, coastal systems are anticipated to be more strongly influenced by continued urbanization, altered instream flows, and population growth in the future. Unfortunately, aquatic toxicology information for diltiazem and many other pharmaceuticals is not available for marine and estuarine organisms, but such field observations suggest that potential adverse outcomes should be examined. Environ Toxicol Chem 2016;35:983–995. © 2015 SETAC